Garbage management capability of local administrative organizations in Ranong Province - Changkid, Pariwat (Local Administration Journal, 2020)
This research aimed to explain the waste management problem in Ranong province as a border town and to analyze the waste management potential of local governments in Ranong in four dimensions: personnel, budget, management, and materials. Using field research, the author collected data via observations, document research, and in-depth interviews with 15 key informants from the local governments in Ranong and 10 citizens in the area. The author used content analysis, triangulation technique, and descriptive interpretation to analyze data and present the findings. The research found that the waste management problem is common in border towns and Ranong also has this problem. Local governments in Ranong province have the potential for waste management in terms of personnel, budget, and materials, but still lacks an effective management system. This study reflects the need for a unique form of waste management for the area and recommends the establishment of an agency to research and develop innovative waste management in all border towns.